The Impact of Carbon Emissions on the Green Economy and Sustainable Development in BRIIJC Countries - Rusiadi; Muhammad Yusuf; Aliza Adivia (International Forum of Researchers and Lecturers, 2023)
Increasing carbon emissions have the unintended consequence of worsening environmental quality as a result of the use of fossil fuels for green economic activities. The green economy concept is being applied in relation to social and economic difficulties, as well as sectors in one of the global strategic areas aimed at overcoming very rapid climate change. The green economy's quality is determined by CO2 emission levels and creates sustainable development, which can improve environmental quality in some countries (Brazil, Russia, India, Indonesia, Japan, and China), particularly during epidemics. In data analysis, various test procedures are utilized. According to the study findings, there was a considerable increase in CO2 emissions in the BRIIJC country during Covid 19, which had an impact on environmental quality, culminating in ozone layer depletion and climate change. The implementation of a green economy can affect environmental circumstances by requiring economic operations to use more ecologically friendly energy, and boosting energy can boost economic growth.